The Comparative Study of Reduplication Between English and Indonesian Language - Akhmad Wildan Habibi (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2021)
This reasearch tries to find out the word from English and Indonesian language which have reduplication word. In the communication process, reduplication word always used in our daily activty. The data of this written were taken form dictionary and oral communication. The researcher compares both of the language to find the similarities and differnces from the reduplication process by using descriptive qualitavite method. The reduplication shows the change of word identity and category like in full reduplication (bye-bye, buku-buku), reduplication with vowel changes (zig-zag, bolak-balik), and reduplication with consonant changes (walkie-talkie, sayur-mayur). The basic form of the word is always present in language use, the meaning of the basic form of the word is always related to the meaning of the word affixed. Then the words after having reduplication process have a new meaning specially in English and Indonesian language.